Nitrogen and Phosphorus Signaling and Transport During Legume–Rhizobium Symbiosis - Ma, Yanlin; Chen, Rujin (Frontiers in Plant Science, 2021)
Nitrogen (N) and phosphorus (P) are two predominant mineral elements not only required for plant growth and development in general, but also playing a key role during symbiotic nitrogen fixation in legumes. Legume plants have evolved complex signaling networks to respond to both external and internal levels of these macronutrients to optimize symbiotic nitrogen fixation in nodules. This involves both long-distance, systemic and local responses. Inorganic phosphate (Pi) and nitrate (NO3-) are two major forms of phosphorus and nitrogen sources that plants utilize and there appears to have an antagonistic crosstalk between Pi and NO3-, involving both transcriptional and posttranscriptional regulatory processes. Much of N and P signaling and transport processes has been investigated in model organisms such as Arabidopsis thaliana and rice (Oryza sativa). We attempted to discuss some of these processes, where appropriate, to serve as references for better understanding of N and P signaling and transport during legume-rhizobium symbiosis.